Game Based Learning Model in PAI Subjects in 2023-2024: A Literature Review - Arum Septiani, Ayu; Gilang Maulana Jamaludin (Departement of PAI, Universitas Majalengka, 2025)
This study aims to analyze and review the literature related to the application of the Game Based Learning (GBL) learning model in Islamic Religious Education (PAI) subjects in 2023-2024. With the rapid development of technology, the use of games as a learning tool is expected to increase students' motivation and understanding of Islamic Religious Education (PAI) materials. Through a literature study approach, this study collects and evaluates various previous studies that discuss the effectiveness of Game Based Learning (GBL) in the context of religious education, as well as the implementation of this model in PAI learning in schools. The results of the study show that GBL can increase student involvement, strengthen understanding of religious materials, and develop critical thinking skills. In addition, challenges in the implementation of GBL in PAI include limited resources and technological readiness in several schools. This research is expected to provide insight into the development of innovative and interesting learning in the field of Islamic Religious Education, as well as provide recommendations for the optimal use of GBL in PAI learning in the future.